Klimat i kultura szkoły a zachowania problemowe uczniów - Okulicz-Kozaryn, Katarzyna (Wydawnictwo Naukowe UAM, 2013)
The aim of the project was to assess the relationship between school culture/climate and students’ problem behaviours. An anonymous questionnaire survey was conducted among second grade students from 4 junior high schools in Warsaw (n = 282). The cross-school comparisons showed significant differences in school culture (indicated by students’ socio-demographic characteristics), school climate (indicated by rates of students who like their school and behavioural norms), students’ functioning (indicated by the school load), leading to a varying prevalence of problem behaviours. A logistic regression analysis indicated the most significant risk factors related to school culture (focus on students’ achievements), climate (negative student-teacher relationships and positive relationships among students) and students school functioning (low school load and frequent truancy). The study results suggest the adoption of prevention guidelines, strengthening in particular teachers’ skills and involvement.
School Culture and Climate vs. Students’ Problem Behaviours
Keywords: school’s climate; school’s culture; adolescents; problem behaviours